(3TQM eNJUQ Yde GdJfLje heYQaI GdJbhjes - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3aEf GdeNJUQ GdPi Cdag ai Yde GdJfLje heYQag GdJbhje GdEeGe GdeMbb GdajdSha GdeObb fUjQ GdOjf GdWhSi s
(3BNQgG (B:s
(3aGdefGSH ddHjY chf GdbeQ efUQakG Yf SYO hddeTJQi chfg eJUdkG HSYO s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
Keywords: (3Gdadcs